An institutional ethnographic analysis of public and patient engagement activities at a national health technology assessment agency. (9th February 2021) - Bidonde, Julia; Vanstone, Meredith; Schwartz, Lisa; Abelson, Julia
Abstract: Objective: The practice of public and patient engagement (PPE) in health technology assessment (HTA) has spread worldwide, yet gaps in knowledge remain. We carried out an institutional ethnography of the Canadian Agency for Drugs and Technologies in Health (CADTH) public and patient involvement in HTA. Methods: The research took place over 15 months and included observational work in the institutional settings, text review, and interviews with individuals working for or involved with the agency. Results: We found that despite demonstrated commitment to PPE, organizational history, governance structure, and practices were impediments to a unified approach to PPE. Unclear role descriptions for committee members and differences in philosophy and priority given to PPE across the organization presented challenges to effective participation. The high degree of value given to evidence-based principles at times conflicted with meaningful integration of patient input. A lack of clear goals and processes, roles, and differential treatment of evidence in PPE served to minimize the importance of patient experiences and to displace their validity. An acknowledgment of conflicts between multiple epistemic traditions at work within HTA activities may strengthen organizational approaches to PPE. Conclusion: HTA organizations can learn from this study by reflecting on the challenges described and the recommendations offered to address them. We suggest solidifying CADTH's commitment to PPE with clear agency-wide roles and direction, values, and outcomes, a comprehensive framework, and policy and procedures. An acknowledgment of diverse epistemic traditions, as well as leadership and expertise in PPE, will strengthen CADTH's PPE activities and sustain its leadership position in the HTA field.